Impacts of Grazing on the Selected Features of Herbaceous Species and Harvested Dry Matter Yield of Natural Pasture - Alemu Gashe Desta; Shashie Ayele Yimenu; Workinesh Tiruneh Teshale; Berhanu Alemu Tessema; Mesganaw Addis Tessma (International Journal of Forestry Research)
This study evaluated how grazing influenced the specific features of herbaceous species (basal cover, species richness, evenness, and diversity) as well as dry matter yield in the northwestern highlands of Ethiopia. For this study, the natural pastures were divided into three strata based on grazing types (grazing exclusion areas, controlled grazing, and continuous grazing). The areas in each grazing type were divided into two randomly selected (100 m × 50 m) sampling blocks. Then, each of the separated areas was divided into five 10 m × 10 m, and in each subdivided plot, (0.5 m × 0.5 m) were placed across the plots. Thus, a total of 30 (0.5 m × 0.5 m) quadrats were used to evaluate the effect of grazing on the basal cover, species richness, diversity, and dry matter yield of the herbaceous pasture layers. As the results showed, there were significant differences in dry matter yield, basal cover, species richness, evenness, and diversity among grazing areas. The dry matter yield, basal cover, species richness, and diversity were significantly (P<0.05) higher in both grazing exclusion and controlled grazing areas than in continuous grazing areas. Therefore, to increase the dry matter yield of natural pasture and to ensure sustainable livestock production, the livestock producers in the study areas should practice either a cut-carry system or a controlled grazing system.